2017
DOI: 10.1039/c7cc04764a
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(iv) oxaliplatin–peptide conjugates targeting memHsp70+ phenotype in colorectal cancer cells

Abstract: Novel Pt(iv) tumour penetrating peptide (TPP) conjugates are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…After loading PFP and BLM, MTN were encapsulated by endogenous red blood cell membrane (RBCm) to prevent drug leaking and attain long circulation in vivo . Finally, TKD, polypeptide derived from the N‐terminal sequence of Hsp70 (TKDNNLLGRFELSG, aa 450–463) and specifically recognizing Hsp70 highly expressed on the surface of HT‐29 cancer cells, was conjugated on RBCm‐MTN‐BLM‐PFP (RMPB) to obtain an active targeting delivery system TKD@RMPB (Figure ). When TKD@RMPB NPs arrived at tumor tissue, US stimulation induced MTN collapse and drug release.…”
Section: Introductionsupporting
confidence: 92%
“…After loading PFP and BLM, MTN were encapsulated by endogenous red blood cell membrane (RBCm) to prevent drug leaking and attain long circulation in vivo . Finally, TKD, polypeptide derived from the N‐terminal sequence of Hsp70 (TKDNNLLGRFELSG, aa 450–463) and specifically recognizing Hsp70 highly expressed on the surface of HT‐29 cancer cells, was conjugated on RBCm‐MTN‐BLM‐PFP (RMPB) to obtain an active targeting delivery system TKD@RMPB (Figure ). When TKD@RMPB NPs arrived at tumor tissue, US stimulation induced MTN collapse and drug release.…”
Section: Introductionsupporting
confidence: 92%
“…Envisioning a new precise therapy for colorectal cancer, Griffith and co-workers reported the monoand di-conjugation of a succinic acid-modified Pt(IV) prodrug of oxaliplatin to a tumour-penetrating peptide of sequence TKDNNLLGRFELSG that can specifically target the membranebound form of the heat shock protein 70 (memHSP70). 63 In vitro, both conjugates showed far superior cytotoxicity and internalization than free oxaliplatin against a resistant colorectal cancer cell line that overexpresses the stated protein (memHSP70+ HT29 cells). In particular, the di-conjugate was more active than the mono-conjugate whereas analogues containing a scrambled peptide sequence abolished the observed cytotoxicity, suggesting the high potential of this peptide to deliver oxaliplatin directly to memHSP70+ tumours.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…In particular, the di-conjugate was more active than the mono-conjugate whereas analogues containing a scrambled peptide sequence abolished the observed cytotoxicity, suggesting the high potential of this peptide to deliver oxaliplatin directly to memHSP70+ tumours. 63 It is known that several types of cancers as well as the endothelial cells of tumour angiogenic vessels overexpress some membrane proteins such as integrins ( particularly the α v β 3 and α v β 5 subtypes) and aminopeptidases, capable of recognizing a broad range of peptides containing RGD or NGR motifs, respectively. Therefore, aiming to attain a redox-responsive tumour-targeted therapeutic approach, Lippard and coworkers reported a series of conjugates of a succinic acidmodified Pt(IV) prodrug of cisplatin to one or two linear/cyclic peptides that target the abovementioned proteins (either RGD, cyclic(CRGDC), cyclic(RGDfK) or NGR, where f represents D-phenylalanine).…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…Gehrmann et al [ 111 ] reported that TPP, an HSP70-derived 14-mer peptide, could rapidly bind to an epitope in the oligomerization domain of HSP70 and be taken up by internalization, suggesting that TPP may have the potential to target cancer cells that express HSP70. Based on this hypothesis, McKeon et al [ 112 ] combined oxaliplatin with TPP to synthesize a novel Pt(IV) prodrug. This complex targeted cancer cells through specific binding and internalization by memHSP70 + tumor cells.…”
Section: Bifunctional Pt(iv) Prodrugsmentioning
confidence: 99%